SKILLS OF BULGARIAN MEDICAL STUDENTS TO PRESCRIBE ANTIBACTERIAL DRUGS RATIОNALLY: A PILOT STUDY - Andrey Petrov (Journal of IMAB, 2018)
Purpose: The purpose of this study was to evaluate the perception of medical students of their level of knowledge about rational drug prescribing and compare this to the evaluation of their practical ability of rational antibiotic prescribing. Materials/Methods: Medical students in their 10th semester of education from the Medical University of Sofia were asked to complete a self-assessment questionnaire containing 5 questions about their knowledge of rational drug prescribing. After that, they were presented with three simulated patient cases with infectious diseases and were asked to prescribe appropriate therapy. The prescribing competencies of the medical students were assessed by two clinical pharmacologists taking into account three criteria: appropriateness of the drugs chosen for the specific patient cases; appropriateness of drug doses and dosing regimens and conformity of written prescriptions with the accepted rules in Bulgaria. Results: The results obtained showed that 19.15% of the medical students rated their theoretical and practical knowledge about rational antibiotic prescribing as “good”, 65.96% as “satisfactory” and 14.89% as “unsatisfactory”. The student’s practical skills to prescribe antibiotics rationally as assessed independently by two clinical pharmacologists showed that 50.35% of the written prescriptions were rated as “good”, 21.64% as “satisfactory” and 28.01% as “unsatisfactory”. Conclusions: Medical students from the Medical University of Sofia showed an acceptable level of competence to choose and prescribe antibiotics rationally. The factors leading to irrational drug prescribing should be thoroughly analyzed to enable additional improvement of their prescribing skills.